PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PRIMA KRISTA SEJAHTERA BANDUNG - Yulistria, Resti; Handayani, Eka Putri; Nurmalsari, Tiara (EDUTECH CONSULTANT, 2018)
Human resources within a company's organization is a unity that can not be separated. Labor discipline for employees is the creation of a pleasant working atmosphere so that will increase the spirit of work in carrying out the work. Performance is one of the work that is charged to employees in completing the work to achieve employment targets. The research method used in making this Final Project is a quantitative method by processing data from the results of questionnaires using the SPSS Version 22 application program.Based on the calculation, the value of correlation coefficient is 0.903 which means very strong and has a positive relationship between labor discipline on employee performance. Labor discipline affects employee performance of 81.5% and the remaining 18.5% is influenced by other factors.The result of regression equation equal to Y=-4,054+0,804X means that is addition of 1% labor discipline, so that the performance value decreased to 4,054.